2016
DOI: 10.1002/aoc.3603
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally friendly and highly efficient synthesis of benzoxazepine and malonamide derivatives using HPA/TPI‐Fe3O4 nanoparticles as recoverable catalyst in aqueous media

Abstract: A magnetic inorganic-organic nanohybrid material (HPA/TPI-Fe 3 O 4 NPs) was produced as an efficient, highly recyclable and eco-friendly catalyst for the one-pot multi-component synthesis of malonamide and 2,3,4,5-tetrahydrobenzo[b] [1,4] oxazepine derivatives with high yields in short reaction times (25-35 min) in aqueous media at room temperature. The nanohybrid catalyst was prepared by the chemical anchoring of H 6 P 2 W 18 O 62 onto the surface of modified Fe 3 O 4 nanoparticles (NPs) with N-[3-(triethoxys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In 2016, research from Babazadeh and colleagues found that the magnetic inorganic‐organic nanohybrid material (HPA/TPI‐Fe 3 O 4 nanoparticles) could act as an efficient and recyclable catalyst for the one‐pot synthesis of malonamides 70 (the same structural malonamides accessed by Shaabani in 2010, method not included in Scheme 14). [36] Their method benefits from high reaction yields (8 examples, yields up to 95 % observed), short reaction times (25–35 min) and the use of water as reaction media, identified as a green solvent [12] . The advantage of employing such magnetic catalysts is that they can be easily recovered.…”
Section: Synthesis Of Malonamidesmentioning
confidence: 99%
“…In 2016, research from Babazadeh and colleagues found that the magnetic inorganic‐organic nanohybrid material (HPA/TPI‐Fe 3 O 4 nanoparticles) could act as an efficient and recyclable catalyst for the one‐pot synthesis of malonamides 70 (the same structural malonamides accessed by Shaabani in 2010, method not included in Scheme 14). [36] Their method benefits from high reaction yields (8 examples, yields up to 95 % observed), short reaction times (25–35 min) and the use of water as reaction media, identified as a green solvent [12] . The advantage of employing such magnetic catalysts is that they can be easily recovered.…”
Section: Synthesis Of Malonamidesmentioning
confidence: 99%
“…There are a large number of reports on the applications of magnetic nanoparticles (MNPs) in industry and chemistry . Fe 3 O 4 coated as a magnet core and supported by organic compounds has found a special place in the synthesis of heterogeneous magnetic nanocatalysts as such many relevant studies have been carried out in this regard . In addition, Fe 3 O 4 supported and coated can create complexes with different metals and synthesized magnetic organometallic nanocatalysts .…”
Section: Introductionmentioning
confidence: 99%